2021
DOI: 10.1111/pce.14169
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones affect phosphorus acquisition strategies in tomato plants

Abstract: Strigolactones (SLs) are plant hormones that modulate morphological, physiological and biochemical changes as part of the acclimation strategies to phosphorus (P) deficiency, but an in-depth description of their effects on tomato P-acquisition strategies under P shortage is missing. Therefore, in this study, we investigate how SLs impact on root exudation and P uptake, in qualitative and quantitative terms over time, in wild-type and SL-depleted tomato plants grown with or without P. Under P shortage, SL-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 59 publications
(90 reference statements)
5
22
0
Order By: Relevance
“…The key genes, triad IPS1-miR399-PHO2 and the high-affinity P transporter LePT2, were involved in the response of tomato plants to low P availability (Gamir et al, 2020). No matter growing with P or not, SL biosynthesis-deficient tomato mutant could not efficiently activate most mechanisms associated with the P starvation response compared with wild-type plants (Santoro et al, 2021).…”
Section: Improvement Of Nutrient Acquisitionmentioning
confidence: 99%
“…The key genes, triad IPS1-miR399-PHO2 and the high-affinity P transporter LePT2, were involved in the response of tomato plants to low P availability (Gamir et al, 2020). No matter growing with P or not, SL biosynthesis-deficient tomato mutant could not efficiently activate most mechanisms associated with the P starvation response compared with wild-type plants (Santoro et al, 2021).…”
Section: Improvement Of Nutrient Acquisitionmentioning
confidence: 99%
“…First-strand cDNA was synthesized from 500 ng of purified total RNA using the High-Capacity cDNA Reverse-Transcription Kit (Applied Biosystems, Monza, Italy) according to the manufacturer's instructions. The specific primer pairs are the same as reported in Santoro et al (2021). The quantitative reverse-transcriptase PCR (qRT-PCR) reactions were carried out in a StepOnePlus system (Applied Biosystems) using the SYBR Green (Applied Biosystems) method.…”
Section: Gene Transcript Quantificationmentioning
confidence: 99%
“…The involvement of SLs in the regulation of plant responses to P deficiency likely occurs through their crosstalk with other phytohormones, such as cytokinins, auxin and ethylene, thus highlighting a complex network of hormonal signals involved in response to P scarcity (Kapulnik et al 2011;Villaécija-Aguilar et al 2019). Recently, we have reported that SLs partly mediate several physiological and morphological changes triggered by P deficiency (Santoro et al 2020(Santoro et al , 2021. We have observed that SL-depleted tomato plants differ from wild-type (WT) controls at the level of root morphology, as many root traits were more severely affected at low P provision (80 μM) (Santoro et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations